Spatial organization of translation and translational repression in two phases of germ granules. - Ramat, A.; Haidar, A.; Garret, C.; Simonelig, M. (Nature communications, 2024)
Most RNA-protein condensates are composed of heterogeneous immiscible phases. However, how this multiphase organization contributes to their biological functions remains largely unexplored. Drosophila germ granules, a class of RNA-protein condensates, are the site of mRNA storage and translational activation. Here, using super-resolution microscopy and single-molecule imaging approaches, we show that germ granules have a biphasic organization and that translation occurs in the outer phase and at the surface of the granules. The localization, directionality, and compaction of mRNAs within the granule depend on their translation status, translated mRNAs being enriched in the outer phase with their 5'end oriented towards the surface. Translation is strongly reduced when germ granule biphasic organization is lost. These findings reveal the intimate links between the architecture of RNA-protein condensates and the organization of their different functions, highlighting the functional compartmentalization of these condensates.